Identification of Sox2 and NeuN Double-Positive Cells in the Mouse Hypothalamic Arcuate Nucleus and Their Reduction in Number With Aging - Sugiura, Ayumu; Shimizu, Tatsuhiro; Kameyama, Takeshi; Maruo, Tomohiko; Kedashiro, Shin; Miyata, Muneaki; Mizutani, Kiyohito; Takai, Yoshimi (Frontiers in Aging Neuroscience, 2021)
The hypothalamus plays a central role in homeostasis and aging. The hypothalamic arcuate nucleus (ARC) controls homeostasis of food intake and energy expenditure and retains adult neural stem cells (NSCs)/progenitor cells. Aging induces the loss of NSCs and the enhancement of inflammation, including the activation of glial cells in the ARC, but aging-associated alterations of the hypothalamic cells remain obscure. Here, we identified Sox2 and NeuN double-positive cells in a subpopulation of cells in the mouse ARC. These cells were reduced in number with aging, although NeuN-positive neuronal cells were unaltered in the total number. Diet-induced obesity mice fed with high-fat diet presented a similar hypothalamic alteration to aged mice. This study provides a new insight into aging-induced changes in the hypothalamus.